Selection criteria of zeotropic mixtures for subcritical organic Rankine cycle based on thermodynamic and thermo-economic analysis. (5th November 2020) - Miao, Zheng; Li, Zihang; Zhang, Kai; Xu, Jinliang; Cheng, Yongpan
Highlights: Thermodynamic and thermo-economic analyses are carried out. Selection criteria of zeotropic mixtures for the closed heat source are proposed. Heat source temperature drop is considered in the selection criteria. Selected mixtures show high thermodynamic and thermo-economic performance. Abstract: The thermodynamic performance of an organic Rankine cycle can be improved effectively with zeotropic mixtures instead of pure fluid; however, it is quite challenging for the selection of zeotropic mixture to achieve the optimal thermodynamic and thermo-economic performance due to the lack of selection criteria. In this study, the thermodynamic and thermos-economic performance is evaluated in terms of overall exergy efficiency and the levelized energy cost respectively. The criteria for the selection of the optimal zeotropic mixture is revisited. It is found that our previously proposed criteria based on thermodynamic analysis for open heat source also holds for the thermo-economic analysis. Furthermore, the study for the effect of temperature drop on the selection of mixtures is carried out for the closed heat source. It is revealed that the heat source temperature drop can be divided into large, small, and transition regions, and the criteria for selection of optimal zeotropic mixture is proposed for each region. The thermo-economic analysis shows that the optimal thermodynamic and thermo-economic performance can be obtained simultaneously in the ORC system with the proposed selection criteria.